Becoming Citizens in a Changing World IEA International Civic and Citizenship Education Study 2016 International Report - Schulz, Wolfram (Springer International Publishing, 2018)
This open access book presents the results from the second cycle of the IEA International Civic and Citizenship Education Study (ICCS 2016). Using data from 24 countries in Asia, Europe and Latin America, the study investigates the ways in which young people are prepared to undertake their roles as citizens in a range of countries in the second decade of the 21st century. It also responds to the enduring and emerging challenges of educating young people in a world where contexts of democracy and civic participation continue to change. New developments of this kind include the increase in the use of social media by young people as a tool for civic engagement, growing concerns about global threats and sustainable development, as well as the role of schools in fostering peaceful ways of interaction between young people. Besides enabling the evaluation of a wide range of aspects of civic and citizenship education, including those related to recent developments in a number of countries, the inclusion of test and questionnaire material from the first cycle of the study in 2009 allows the results from ICCS 2016 to be used to examine changes in civic knowledge, attitudes and engagement over seven years. .